The Use of Shape Memory Alloys in Cages for Cervical Spinal Surgery - Arlt, F.; Winkler, D.; Knoop, N.; Weidling, M.; Frank, F.; Meixensberger, J.; Grunert, R. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Background Degenerative changes in the cervical spine can include the gradual loss of functionality of the intervertebral disks, development of osteophytes and ligament hypertrophy. Removal of the intervertebral disk and replacement with a cage (anterior discectomy and fusion [ACDF]) is a standardized operative procedure in these patients. The implant should provide structural support, should restore the physiologic lordosis, and enable a solid fusion. In this context, shape memory materials have great potential in the development of implants in spinal surgery.Methods We designed and developed a cage that automatically adapts to the cross-section of the intervertebral disk space and simultaneously ensures mechanical support for load transfer between the adjacent vertebral bodies. A special mechanism (shape memory alloy [SMA]) should allow the implant to adapt to the geometric configuration of the intervertebral disk space. The cage developed was tested in an artificial cervical spine.Results The base body of the cage consists of polyether ether ketone (PEEK) with a width of 14 mm, length of 16 mm, and height of 4 mm. A shape memory actuator, made of nickel–titanium alloy, is used to realize the geometry adaptation. Utilizing this, the transformation from martensite to austenite is completed at 35°C. Biomechanical testing with lateral bending and compression was performed. Subsequent cyclic loading results in a constant hysteresis curve, indicating stable implant positioning.Conclusions We feel confident about having developed an alternative cage for ACDF that can potentially reduce peri- and postoperative morbidity and provide long-term stability by reducing bone removal during cage implantation. Therefore, we are encouraged to proceed with further biomechanical testing in cadaver specimens to eventually reach the goal of in vivo application.
Keywords: cervical spine surgery; cervical disk fusion; shape memory alloys